Development and Validation of the Air Medical Prehospital Triage Score for Helicopter Transport of Trauma Patients. Issue 2 (August 2016) - Brown, Joshua B.; Gestring, Mark L.; Guyette, Francis X.; Rosengart, Matthew R.; Stassen, Nicole A.; Forsythe, Raquel M.; Billiar, Timothy R.; Peitzman, Andrew B.; Sperry, Jason L.
Abstract : Objective: The aim of this study was to develop and internally validate a triage score that can identify trauma patients at the scene who would potentially benefit from helicopter emergency medical services (HEMS). Summary Background Data: Although survival benefits have been shown at the population level, identification of patients most likely to benefit from HEMS transport is imperative to justify the risks and cost of this intervention. Methods: Retrospective cohort study of subjects undergoing scene HEMS or ground emergency medical services (GEMS) in the National Trauma Databank (2007–2012). Data were split into training and validation sets. Subjects were grouped by triage criteria in the training set and regression used to determine which criteria had a survival benefit associated with HEMS. Points were assigned to these criteria to develop the Air Medical Prehospital Triage (AMPT) score. The score was applied in the validation set to determine whether subjects triaged to HEMS had a survival benefit when actually transported by helicopter. Results: There were 2, 086, 137 subjects included. Criteria identified for inclusion in the AMPT score included GCS <14, respiratory rate <10 or >29, flail chest, hemo/pneumothorax, paralysis, and multisystem trauma. The optimal cutoff for triage to HEMS was ≥2 points. In subjects triaged to HEMS, actual transport by HEMS was associated with an increased odds of survival (AOR 1.28; 95% confidence interval [CI] 1.21–1.36, P  < 0.01). In subjects triaged to GEMS, actual transport mode was not associated with survival (AOR 1.04; 95% CI 0.97–1.11, P  = 0.20). Conclusions: The AMPT score identifies patients with improved survival following HEMS transport and should be considered in air medical triage protocols.